Road condition monitoring by IRI using sensors implemented on an ATV - Guerra, Kevin (2024)
The poor condition of a road causes wear in the mechanics of a vehicle, higher probability of accidents, more traffic and tire wear. To know the conditions of a road it is necessary to monitor the international regularity index (IRI), this calculation is made with different types of manual or automatic recording devices. In Peru, monitoring is done with different types of equipment that, depending on the budget, use different performance and precision systems. At present, manual measurements are still used, which are low cost, but generate errors in the measurement or the process takes too much time and the need to close roads. In this context, the present work aims to automatically monitor the condition of a road through low-cost sensors implemented in an ATV that allows driving in all types of terrain and easily adaptable to ATVs used for patrolling in Peru. Although there are superior advantages in the use of ATVs for the implementation of sensors and automatic monitoring, they present a high level of unwanted vibration due to their size and weight. The system is composed of wavelet transform and moving average filtering techniques for noise reduction and to improve the captured signal for better IRI calculation. The results of the system experiments show a monitoring level for each 44 m segment for an average time of 75 seconds, which allows to monitor automatically and in a shorter time large lengths of road.